Measurement of the helicity fractions of W bosons from top quark decays using fully reconstructed tt̄ events with CDF II - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We present a measurement of the fractions F0 and F+ of longitudinally polarized and right-handed W bosons in top-quark decays using data collected with the CDF II detector. The data set used in the analysis corresponds to an integrated luminosity of approximately 318pb-1. We select tt̄ candidate events with one lepton, at least four jets, and missing transverse energy. Our helicity measurement uses the decay angle θ*, which is defined as the angle between the momentum of the charged lepton in the W boson rest frame and the W momentum in the top-quark rest frame. The cos θ* distribution in the data is determined by full kinematic reconstruction of the tt̄ candidates. We find F0=0.85-0.22+0.15(stat)±0.06(syst) and F+=0.05-0.05+0.11(stat)±0.03(syst), which is consistent with the standard model prediction. We set an upper limit on the fraction of right-handed W bosons of F+<0.26 at the 95% confidence level. © 2007 The American Physical Society.